2023
DOI: 10.1002/cnr2.1890
|View full text |Cite
|
Sign up to set email alerts
|

Survival and predictors of mortality among acute leukemia patients on follow‐up in Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia: A 5‐year retrospective cohort study

Bargude Balta,
Tigistu Gebreyohannis,
Erdaw Tachbele

Abstract: BackgroundAlthough Ethiopia has more than 78% of leukemia cases and a significant burden of the disease, the survival of leukemia patients in the country is poorly recognized. The purpose of this study was to assess the survival and predictors of acute leukemia patients.MethodsA 5‐year retrospective cohort study was conducted including all acute Leukemia patients who visited Tikur Anbessa Specialized Hospital between January 2015 and December 2019. Data were retrieved from patient's medical records between Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Leukemia-related mortality varied less by region globally. Most parts of Asia, Europe, America, Australia, and New Zealand recorded death rates between 2.5 and 4.0 per 100,000 people [6][7][8]. The worldwide cancer research organization revealed that by 2023, there would be 2.4 additional instances per 100,000 people, and the fatality rate will be increased to between 1.4 and 1.8 per 100,000 people.…”
Section: Introductionmentioning
confidence: 99%
“…Leukemia-related mortality varied less by region globally. Most parts of Asia, Europe, America, Australia, and New Zealand recorded death rates between 2.5 and 4.0 per 100,000 people [6][7][8]. The worldwide cancer research organization revealed that by 2023, there would be 2.4 additional instances per 100,000 people, and the fatality rate will be increased to between 1.4 and 1.8 per 100,000 people.…”
Section: Introductionmentioning
confidence: 99%